Borylative Radical Cyclizations of Benzo[3, 4]cyclodec‐3‐ene‐1, 5‐diynes and N‐Heterocyclic Carbene‐Boranes. Issue 23 (27th March 2017) - Watanabe, Takashi; Hirose, Daisuke; Curran, Dennis P.; Taniguchi, Tsuyoshi
Abstract: Borylative radical cyclization of benzo[3, 4]cyclodec‐3‐ene‐1, 5‐diynes to provide 5‐borylated 6, 7, 8, 9‐tetrahydrobenzo[ a ]azulenes has been developed. The experimental results suggest that the reaction proceeds by a radical chain mechanism, in which di‐ tert ‐butyl hyponitrite (TBHN) works as a good radical initiator to form boryl radicals from N‐heterocyclic carbene–boranes (NHC‐boranes). The present reaction is a rare model that illustrates addition of boryl radicals to alkynes. Abstract : Radicalized boranes : Addition of boryl radicals to alkynes occurs when a mixture of strained benzo[3, 4]cyclodec‐3‐ene‐1, 5‐diynes and N‐heterocyclic carbene–boranes are exposed to radical conditions with di‐ tert ‐butyl hyponitrite. The addition reaction induces subsequent radical cyclization to provide 5‐borylated 6, 7, 8, 9‐tetrahydrobenzo[ a ]azulenes. Further transformation of the borylated compound has been achieved by using a modified procedure of the Suzuki–Miyaura reaction.